Value of whole‐genome sequencing to Australian cancer patients and their first‐degree relatives participating in a genomic sequencing study. Issue 1 (3rd July 2021) - Butow, Phyllis; Davies, Grace; Napier, Christine E.; Bartley, Nicci; Ballinger, Mandy L.; Biesecker, Barbara; Juraskova, Ilona; Meiser, Bettina; Schlub, Timothy; Thomas, David M.; Goldstein, David; Best, Megan C.; et al.
Abstract: Genomic Sequencing (GS) to identify high cancer risk will soon enter clinical practice at significant cost to the health system. This study aimed to quantify perceived value of GS to Australian cancer patients and their first‐degree relatives participating in a genomic sequencing study, and factors associated with value. Participants were recruited upon consent to the genomics study. Eligible participants (with cancer of likely genetic etiology, or a first‐degree relative) completed a questionnaire prior to GS. Willingness to pay was assessed via hypothetical trade‐off scenarios of actionable result return rates of 1%, 10%, 20%, 30%, 40% or 50%. Of 348 probands and 213 relatives (92% and 93% response rate), 81% would consistently have GS for as little as a 1% actionable return rate. Participants would pay a median of $1, 000 for return rates of at least 20% (probands) or 30% (relatives), and $300 for lower return rates. Probands with common cancers and negative attitudes to uncertainty were more likely to have GS; those with higher education were more willing to pay $1, 000 and $3, 000 for lower return rates. This study found high interest in, but lower willingness to pay for GS in cancer patients and their first‐degree relatives, possibly due to inability to pay. Further research is needed to improve our understanding of how individuals in different risk circumstances, trade‐off the risks, harms, and benefits of GS.